2018
DOI: 10.1371/journal.pone.0195480
|View full text |Cite
|
Sign up to set email alerts
|

Natural regeneration on seismic lines influences movement behaviour of wolves and grizzly bears

Abstract: Across the boreal forest of Canada, habitat disturbance is the ultimate cause of caribou (Rangifer tarandus caribou) declines. Habitat restoration is a focus of caribou recovery efforts, with a goal to finding ways to reduce predator use of disturbances, and caribou-predator encounters. One of the most pervasive disturbances within caribou ranges in Alberta, Canada are seismic lines cleared for energy exploration. Seismic lines facilitate predator movement, and although vegetation on some seismic lines is rege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 77 publications
5
36
0
Order By: Relevance
“…Outside of protected areas, we found that predation risk increased closer to seismic lines across all three spatio‐temporal scales of habitat use. Previous research has shown that seismic lines are used by bears and wolves (Dickie et al., 2019; Finnegan, Pigeon, et al., 2018; Tigner et al., 2014), increase predator travel speeds and encounter rates with prey (Dickie, Serrouya, McNay, et al., 2017; McKenzie et al., 2012; Mumma et al., 2017), and are a source of forage for primary prey species (e.g., moose) and bears (Finnegan, MacNearney, et al., 2018). By assessing habitat use prior to predation‐caused caribou mortalities, our results provide direct evidence that predation risk for caribou is higher near seismic lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside of protected areas, we found that predation risk increased closer to seismic lines across all three spatio‐temporal scales of habitat use. Previous research has shown that seismic lines are used by bears and wolves (Dickie et al., 2019; Finnegan, Pigeon, et al., 2018; Tigner et al., 2014), increase predator travel speeds and encounter rates with prey (Dickie, Serrouya, McNay, et al., 2017; McKenzie et al., 2012; Mumma et al., 2017), and are a source of forage for primary prey species (e.g., moose) and bears (Finnegan, MacNearney, et al., 2018). By assessing habitat use prior to predation‐caused caribou mortalities, our results provide direct evidence that predation risk for caribou is higher near seismic lines.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic disturbance can enhance predation risk by increasing the spatial and temporal overlap between predators and prey (Frey et al., 2017; Whittington et al., 2011), increasing predator travel speeds and hunting efficiency (Dickie et al., 2017; Finnegan, Pigeon, et al., 2018; McKenzie et al., 2012), or decreasing the effectiveness of prey refugia (DeMars & Boutin, 2018; Peters et al., 2013). Anthropogenic disturbance can also increase predation risk through apparent competition, where habitat change alters the abundance and distribution of primary prey, resulting in an increased abundance and distribution of predators and increased predation rates for secondary prey species (DeCesare et al., 2010; Latham et al., 2011; Robinson et al., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…, DeMars and Boutin ), and recovering vegetation on LFs provides more key bear food than the interior forest (Finnegan et al. ). Thus, incidental bear predation on caribou could be reduced to some degree by LF restoration, unless vegetation on former LFs still provides more bear food.…”
Section: Discussionmentioning
confidence: 99%
“…Whether LF restoration would reduce bear predation on caribou is still under research. Bears use LFs as traveling paths (Tigner et al 2014, DeMars andBoutin 2018), and recovering vegetation on LFs provides more key bear food than the interior forest (Finnegan et al 2018). Thus, incidental bear predation on caribou could be reduced to some degree by LF restoration, unless vegetation on former LFs still provides more bear food.…”
Section: Discussionmentioning
confidence: 99%
“…For terrain, we used a LiDAR-derived depth to water estimation, a metric of soil wetness based on local topography and modeled hydrologic flow [67,68]. To represent the diminishing effect of the depth to water on vegetation growth, we transformed the variable using an exponential decay function 1 -e −1.55×Depth2Wat(m) [69]. This decay function caused depth to water to Number of transects surveyed in west-central and north-western Alberta, Canada among the five sampling strata during the summers of 2014 and 2015. a partitioned into time-since-disturbance in five year increments.…”
Section: Lichen Absence and Abundancementioning
confidence: 99%